1998
DOI: 10.1021/jf980189m
|View full text |Cite
|
Sign up to set email alerts
|

Bioactive Flavonoids from Endophyte-Infected Blue Grass (Poa ampla)

Abstract: Ethanol extract of leaves of Poa ampla, either infected or uninfected with the symbiotic fungus Neotyphodium typhnium, were tested for bioactivity against the mosquito larvae. Results of these tests indicated that only the extracts obtained from endophyte-infected grass are active against mosquito larvae. Relatively high activity was detected in stromata, seeds, spikelets, and leaves of plants, while only weak or no activity was found in extracts of the isolated fungus. The ethyl acetate fraction had approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 20 publications
1
41
1
Order By: Relevance
“…Hence, N. lolii infection affects only the level of polyphenol expression rather than changing the number or type of polyphenols in L. perenne. Our results contradict with the earlier findings of Ju et al 18 and Ponce et al, 17 who reported significant qualitative along with quantitative changes in the phenolic composition of P. ampla and L. multif lorum infected with their respective Neotyphodium spp. Knowing that not only were different plants used by Ju et al and Ponce et al but different species of Neotyphodium were used as well, we conclude that the influence of endophyte infection on polyphenol composition of grasses is case specific and depends on several factors including, but not restricted to, plant type, endophyte species, and endophyte strain.…”
Section: Journal Of Agricultural and Food Chemistrycontrasting
confidence: 99%
“…Hence, N. lolii infection affects only the level of polyphenol expression rather than changing the number or type of polyphenols in L. perenne. Our results contradict with the earlier findings of Ju et al 18 and Ponce et al, 17 who reported significant qualitative along with quantitative changes in the phenolic composition of P. ampla and L. multif lorum infected with their respective Neotyphodium spp. Knowing that not only were different plants used by Ju et al and Ponce et al but different species of Neotyphodium were used as well, we conclude that the influence of endophyte infection on polyphenol composition of grasses is case specific and depends on several factors including, but not restricted to, plant type, endophyte species, and endophyte strain.…”
Section: Journal Of Agricultural and Food Chemistrycontrasting
confidence: 99%
“…This hypothesis is supported by the observation that endophyteinfected plants of Poa ampla produce this type of compounds (Ju et al 1998). No specific phytochemical information is available to date for Poa bonariensis.…”
Section: Discussionmentioning
confidence: 91%
“…Finally, entophytes have been known to enhance biomass, tiller numbers, seed production, and root growth (Clay 1987;Cheplick et al 1989;Belesky and Fedders 1995) via plant hormone production, increased photosynthetic performance, and reduced transpiration rate (Belesky et al 1987;Clay 1990;Bacon 1993). Some of these benefits to plants due to fungal endophytes are attributed to the production of a diverse range of secondary metabolites such as alkaloids and phenolic-like compounds (Bush et al 1997;Ju et al 1998).…”
Section: Introductionmentioning
confidence: 99%